Advanced Lipotransfer Techniques - Blugerman, Guillermo; Amar, Roger; Schavelzon, Diego; II, Marco A. Pelosi; III, Marco A. Pelosi; Soto, Javier A.; Chomyszyn, Anastasia; Podda, Maurizio; Markowsky, Andrea V.; D’Angelo, Jorge A.; Moreno, Rodrigo (IntechOpen, 2011)
None